Representação religiosa na tradição oral da província de Pasco - La Madrid Vivar, Pablo Lenin (2021)
The objective of this article is to explain the religious representations in the Pasco oral tradition, based on the oral narratives collected in the thirteen districts of the Pasco province. For this reason, the interview was used as a research method, the information was collected in situ, in the different towns that make up the province of Pasco, directly from the elderly and other informants. The study is within the Social Sciences, the result of which was the publication of the first volume of Pasco's oral tradition. The result of the investigation offers us unpublished tales and legends that will shape Pasco's literary prospect.